Gatunkowe poszukiwania we współczesnej kulturze zaangażowanej. Kilka uwag na temat „Patriotyzmu jutra” duetu Siksa - Florczyk, Tomasz (Zagadnienia Rodzajów Literackich, 2019)
The paper is an analysis of the “Siksa” duet’s work, The Patriotism of Tomorrow (2018) deeply rooted in a contemporary feministic punk culture. The author looks at the work from a genre studies perspective, finding a genological novum (basing on E. Balcerzan’s theory of “multimedia genology”). The analysis of the work (a verbal-musical collage), consists of the search for its genological place in contemporary engaged culture. The author demonstrates that the uniqueness of its genre frames is not wide enough to be described as “antigenre” or “authorial genre”, the terms introduced by Polish scientists; he suggests that the term “post-genre” ought to be used instead.